Rain events decrease boreal peatland net CO2 uptake through reduced light availability. (6th March 2015) - Nijp, Jelmer J.; Limpens, Juul; Metselaar, Klaas; Peichl, Matthias; Nilsson, Mats B.; van der Zee, Sjoerd E. A. T. M.; Berendse, Frank
Abstract Boreal peatlands store large amounts of carbon, reflecting their important role in the global carbon cycle. The short‐term exchange and the long‐term storage of atmospheric carbon dioxide (CO2) in these ecosystems are closely associated with the permanently wet surface conditions and are susceptible to drought. Especially, the single most important peat forming plant genus, Sphagnum, depends heavily on surface wetness for its primary production. Changes in rainfall patterns are expected to affect surface wetness, but how this transient rewetting affects net ecosystem exchange of CO2 (NEE) remains unknown. This study explores how the timing and characteristics of rain events during photosynthetic active periods, that is daytime, affect peatland NEE and whether rain event associated changes in environmental conditions modify this response (e.g. water table, radiation, vapour pressure deficit, temperature). We analysed an 11‐year time series of half‐hourly eddy covariance and meteorological measurements from Degerö Stormyr, a boreal peatland in northern Sweden. Our results show that daytime rain events systematically decreased the sink strength of peatlands for atmospheric CO2. The decrease was best explained by rain associated reduction in light, rather than by rain characteristics or drought length. An average daytime growing season rain event reduced net ecosystem CO2 uptake by 0.23–0.54 gC m−2. On an annual basis, this reduction of net CO2 uptake corresponds to 24% of the annual net CO2 uptake (NEE) of the study site, equivalent to a 4.4% reduction of gross primary production (GPP) during the growing season. We conclude that reduced light availability associated with rain events is more important in explaining the NEE response to rain events than rain characteristics and changes in water availability. This suggests that peatland CO2 uptake is highly sensitive to changes in cloud cover formation and to altered rainfall regimes, a process hitherto largely ignored.